Industry-Institute Perceptual Map (PM) and Management Students’ Satisfaction Index (MSSI): A Road Map for Academic Excellence - Prasad, Ram Komal; Verma, Sanjeev (Prabandhan: Indian Journal of Management, 2019)
Purpose: Outstanding experience necessitates more than high-quality products and services for customer satisfaction. Although businesses have realized the importance of customer experience, there are sparse relevant measurement metrics in the management education context. In order to fill the research gap, this study attempted to develop a Management Students’ Satisfaction Index (MSSI). Research Design: Extant literature review was done to identify the relevant constructs for building MSSI. Scientific research design was followed for conducting the study. Structural equation modelling was used for data analysis. Perceptual mapping was also done to understand the relative strength of different formats of management institutions. Findings: MSSI for public universities had a 3.23 index score, private universities scored 3.62, and affiliated institutes scored 3.65, while autonomous bodies had a 3.59 index score. It implies that the affiliated institutions evoked the highest satisfaction levels among students; whereas, public universities had the lowest index score of 3.23. The integrated (combined) index of sampled management institutions worked out to 3.57, which was lower than that of private, affiliated, and autonomous institutes. Implications: MSSI will provide management institutions a strategic framework on key satisfaction drivers of management students. Practitioners may devise a strategy for meaningful alignment of their resources for higher student learning and experience outcomes. Originality: Several customer satisfaction index studies have been developed in different parts of the world, but most of them are generic in nature. Development of Management Students’ Satisfaction Index model (MSSI) is the first ever attempt to develop a students’ satisfaction index.